If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(10 + -2) = (3 * 10) + -1(3 * 2) Combine like terms: 10 + -2 = 8 3(8) = (3 * 10) + -1(3 * 2) Multiply 3 * 8 24 = (3 * 10) + -1(3 * 2) Multiply 3 * 10 24 = (30) + -1(3 * 2) 24 = 30 + -1(3 * 2) Multiply 3 * 2 24 = 30 + -1(6) Multiply -1 * 6 24 = 30 + -6 Combine like terms: 30 + -6 = 24 24 = 24 Add '-24' to each side of the equation. 24 + -24 = 24 + -24 Combine like terms: 24 + -24 = 0 0 = 24 + -24 Combine like terms: 24 + -24 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| -7x+8/2 | | 9x-7x=18 | | 7x+x-4x-7=5x | | 5(k-78)+-96=-51 | | 9x-7x=-30 | | 3.6-x=9 | | -7(q+56)=14 | | 3erty+4erty=5ertyz | | y=6+m(x+5) | | -4=-29u | | -3x+12/2 | | 2/-3x+12 | | 9/5*-30+32 | | j-69/2=9 | | 1+3=x-18 | | 1/2*((5x+6)+(3x))*(4x-3) | | x+(y+5)=-1 | | 5(x-3)=-9(x+1)+29 | | k+1(k^2+5k+6)=0 | | 8X^2-2xy-3y^2=0 | | 9X^2-2xy-3y^2=0 | | 580=3x | | 2(4t-7)/3=-22 | | 2(h+12)/5=10 | | 3x^2-x-13=0 | | 4x^2=-9x-4 | | 12+4(z+3)=3z+2 | | 10+5(z-2)=42+5 | | (12x-8)/4=28 | | y+3=(x-9) | | 12x-8/4=28 | | -13n+4=-12n-12 |